If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -10x = 1333 + -31x Solving 10 + -10x = 1333 + -31x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '31x' to each side of the equation. 10 + -10x + 31x = 1333 + -31x + 31x Combine like terms: -10x + 31x = 21x 10 + 21x = 1333 + -31x + 31x Combine like terms: -31x + 31x = 0 10 + 21x = 1333 + 0 10 + 21x = 1333 Add '-10' to each side of the equation. 10 + -10 + 21x = 1333 + -10 Combine like terms: 10 + -10 = 0 0 + 21x = 1333 + -10 21x = 1333 + -10 Combine like terms: 1333 + -10 = 1323 21x = 1323 Divide each side by '21'. x = 63 Simplifying x = 63
| 1/4x2/4 | | 2k^2-7k-15=0 | | 5x+3=4x-4 | | z^2-z+5=0 | | 4(2-4x)=16 | | 3x=22x | | 3ix-5+3i=(3-1)y+1 | | 7m-2m= | | 53-2x=25x+20 | | 6x+129=16x-11 | | 8-10=2x | | 4u^2+23u+28=0 | | 10x+2=8x+14 | | -2x+4=-4x+2 | | (2x^2y-3y^4)dx+(3x^3+2xy^3)dy=0 | | (2x^2y-3y^4)dx+(3x^3-2xy^3)dy=0 | | 4x+2=-2x+7 | | -3x+7=4x-12 | | (13-6)*(2+5)= | | 45+105+(4x-15)+5x=360 | | 5x+5=2x+9 | | 24=4(2-2x) | | 10x-8=8x+7 | | 4y+12=2y-10 | | 6(7x+1)=43x | | 7x-7=3x+10 | | x^2-((2/3)*x)-(27/16) | | x^2-(2/3x)-(27/16)=0 | | 4U^2-19u+15=0 | | 5x-37=7x+47 | | 3x/5=11 | | 1-4x=22-3x |